Vos(z) de maestro : prácticas narrativas para construir definiciones del rol docente (2018)
To narrate the current school, in the voice of the teachers who have lived and built it from other meanings, allows us to listen from their experiences, the way they have given way to a transformation in different spheres: to talk about the professional, personal, pedagogical the teacher requires him to change his ways of conceiving the school, the classroom, the ways of inhabiting it, of interacting with it and of living it as a principle of relationship, word and action. To affirm that the school is then, the place where the students, their parents, families and other people who could intervene in the educational act agree, is to compromise the vision of the "educational" and how all together create a tissue full of knowledge, experiences, experiences that enrich, exchange and increase other possibilities of training, learning and transformation that results in a space brimming with meanings. In this sense, the experiences, experiences, situations and narratives that are typical of teachers in practice, allow through the text, move from the naturalness of its meaning, from the spontaneity of the facts that being real, are weaving "other" ideas of conceiving school, teacher and education. Through the development of the text, there are some categories that emerge through what we can consider a spontaneous conversation, quiet, simple and language in terms of what each one has built as a life project: Education, Classroom, Student, Teacher , they are some of them, that as they are listened to, they reflect and they write, they weave what for research is called "participant observation" that for the case of the experience that is narrated here, it will be, rather, "observant participation". Thus, the present text shows the multiple ideas of what a teacher means to speak of himself in recognition of his work, his history and his projection in a common space that without being judged, finds the reality outside the theory said for the books